Forensic Glass Investigation in the Hungarian Institute for Forensic Sciences (Academic Journal of Internal Affairs, 2021)
Break-in, vandalism, car burglary – some of the crimes often involving glass breaking, in which physical-chemical expert examinations can help a lot in identifying the offender and solving the crime. In Hungary, the beginning of forensic glass examination dates back to the 1960s. In the nearly six decades since then, the methods used in the investigations have evolved a lot and expanded significantly. In addition to the classical physical parameters on which the comparison was based in the early days, the assessment of determination of origin by the most modern instrumental methods has given better-founded results, and besides it has also been possible to build a database. The aim of our paper is to present, after a brief historical overview, the process of forensic glass examination in the Hungarian Institute for Forensic Sciences, its applied methods, as well as the statements that can be made on the basis of the obtained results. In addition, in the light of a case study, we also illustrate in detail the difficulties and limitations of forensic glass examination.Arrived: 4 August 2020Accepted: 16 Sept 2020
Keywords: expert evidence; glass; forensic identification; elemental composition